Microbiome in cystic fibrosis: Shaping polymicrobial interactions for advances in antibiotic therapy - Susana P. Lopes (2015)
Recent molecular methodologies have demonstrated a complex microbial ecosystem in cystic fibrosis (CF) airways, with a wide array of uncommon microorganisms co-existing with the traditional pathogens. Although there are lines of evidence supporting the contribution of some of those emergent species for lung disease chronicity, clinical significance remains uncertain for most cases. A possible contribution for disease is likely to be related with the dynamic interactions established between microorganisms within the microbial community and with the host. If this is the case, management of CF will only be successful upon suitable and exhaustive modulation of such mixed ecological processes, which will also be useful to predict the effects of new therapeutic interventions.